2008
DOI: 10.1371/journal.pone.0002530
|View full text |Cite
|
Sign up to set email alerts
|

An Open Label, Randomised Trial of Artesunate+Amodiaquine, Artesunate+Chlorproguanil-Dapsone and Artemether-Lumefantrine for the Treatment of Uncomplicated Malaria

Abstract: BackgroundArtesunate+amodiaquine (AS+AQ) and artemether-lumefantrine (AL) are now the most frequently recommended first line treatments for uncomplicated malaria in Africa. Artesunate+chlorproguanil-dapsone (AS+CD) was a potential alternative for treatment of uncomplicated malaria. A comparison of the efficacy and safety of these three drug combinations was necessary to make evidence based drug treatment policies.MethodsFive hundred and thirty-four, glucose-6-phosphate dehydrogenase (G6PD) normal children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 7 publications
0
40
1
Order By: Relevance
“…Rather low levels of drug efficacy had also been reported from two studies in Ghana 30,31 where PCR corrected cure rates at Day 28 were only 86.2% and 88.3%, respectively. In one of these studies only the first dose was given under supervision, whereas in the other study the administration of all 6 tablets was supervised.…”
Section: Discussionmentioning
confidence: 81%
“…Rather low levels of drug efficacy had also been reported from two studies in Ghana 30,31 where PCR corrected cure rates at Day 28 were only 86.2% and 88.3%, respectively. In one of these studies only the first dose was given under supervision, whereas in the other study the administration of all 6 tablets was supervised.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the data are in line with studies conducted in Ghanaian children showing lower parasitological and clinical failure rates in the ASAQ compared with the AL arm. [37][38][39] In contrast, results from Central and East Africa show higher efficacy of AL than ASAQ, especially a higher potency in preventing reinfections. 14,40 In the present study, both treatments were equivalent regarding parasite and fever clearance rates and gametocyte carriage.…”
Section: Discussionmentioning
confidence: 96%
“…29 A trial in Ghana reported PCR-corrected Day 28 parasitological and clinical cure rates (PP population) of 86.3% (138/160) for CPG-DDS + A, 86.2% (131/152) for AL, and 93.4% (141/151) for amodiaquine + A ( P = 0.08). 30 Neither of these studies has reported pfdhfr mutation frequencies, though the authors of the Rwandan study state that a later analysis is planned. 29 There was no difference in re-infection rates between CDA and CPG-DDS.…”
Section: Discussionmentioning
confidence: 99%